The Typewriter Under the Bed: Introducing Digital Humanities through Banned Books and Endangered Knowledge - Bolintineanu, Alexandra; Thirugnanasampanthan, Jaya (KULA, 2018)
In 2017, I taught an Introduction to Digital Humanities course for undergraduate students at the University of Toronto. The course’s unifying theme was banned books. What moved me to focus the course in this way was the illegal typewriter that lived under my childhood bed: I grew up in formerly communist Eastern Europe, where typewriters were tightly controlled by the government. Yet my family owned an illegal, unregistered typewriter, hidden under my bed behind the off-season clothes, because they saw the ability to write and disseminate one’s thoughts as a technology of survival.In the Intro to DH course, students explored the intellectual landscape of the digital humanities by thinking about banned books throughout history. They examined early printed books of astronomy; early printed books of the lives of saints; illicitly typewritten and photographed Soviet samizdat; endangered climate change research data rescued by the Internet Archive; and American Library Association data about banned and challenged books for children and young adults. This article reflects on using the lens of banned books and endangered knowledge to focus an Introduction to DH course and encourage students to interrogate critically how a variety of technologies—from codex to printing press to typewriter to the internet—create, transmit, preserve, and repress knowledge and cultural memory.